The Indonesian Version of the Depressive Symptom Index-Suicidality Subscale: Adaptation and Psychometric Evaluation - Lavenda Geshica; Ferdi Djajadisastra; Sugiarti Sugiarti (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Suicide is a severe health problem currently a global concern that causes approximately 703,000 deaths each year. 75% of suicide occurs at productive age, with university students as subgroups that are prone to experience suicidal thoughts and behaviors. This study aimed to adapt Depressive Symptom Index- Suicidality Subscale (DSI-SS) into the Indonesian language and evaluate its psychometric properties. The International Test Commission (ITC) requirements were used as a reference in the adaptation process. Moreover, to evaluate the psychometric properties, 510 university students from various regions in Indonesia participated in this study. The result showed that the DSI-SS Indonesia version has good psychometric properties. The corrected item-total correlation ranged from 0.837-0.872, with an alpha reliability coefficient of 0.936. The DSI-SS highly correlated with a test that evaluates depression symptoms (the PHQ-9) and a history of suicide attempts. The exploratory factor analysis also supports the validity evidence, indicating that the DSI-SS is a unidimensional scale.